2015
DOI: 10.1111/aej.12132
|View full text |Cite
|
Sign up to set email alerts
|

Root canal filling in primary molars without successors: Mineral trioxide aggregate versus gutta‐percha/AH‐Plus

Abstract: The aim of this study was to compare the clinical and radiographical success of mineral trioxide aggregate (MTA) and gutta-percha/AH-Plus used as a root canal filling material in primary second molars without successors. A total of 16 patients (9 girls, 7 boys) aged 6-13 years (mean: 10.5) were selected and randomly distributed into the treatment groups. Children were recalled for clinical and radiographic examination at 6, 12, 18, 24 and 36 months. Differences in treatment outcomes were analysed using chi-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…However, tooth coloured ProRoot MTA was significantly superior to gutta‐percha + AH Plus root canal sealer as a root filling material in primary molars (Bezgin et al . ). In addition, placement of ProRoot MTA on the pulpal floor of primary teeth with furcation radiolucencies was reported to decrease the healing period (Arikan et al .…”
Section: Root Fillingmentioning
confidence: 97%
“…However, tooth coloured ProRoot MTA was significantly superior to gutta‐percha + AH Plus root canal sealer as a root filling material in primary molars (Bezgin et al . ). In addition, placement of ProRoot MTA on the pulpal floor of primary teeth with furcation radiolucencies was reported to decrease the healing period (Arikan et al .…”
Section: Root Fillingmentioning
confidence: 97%
“…19 If a hermetic seal cannot be maintained through obturation, tissue fluids may enter the canal and provide additional nutrition to any remaining bacteria. 20 Application of stainless steel crowns (SSC) has been recommended after the pulpal treatment of primary teeth. 8 However, in this study, four of the treated teeth were restored with composite resins and SSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a resorbable paste or a combination of pastes such as zinc oxide eugenol (ZOE), iodoform, and calcium hydroxide is used for primary tooth pulpectomy [25]; however, in the case of a primary tooth without a successor, a nonresorbable material is recommended [26, 27]. Previous studies have reported success with a combination of gutta-percha and ZOE sealer [28] and with mineral trioxide aggregate (MTA) [26, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported success with a combination of gutta-percha and ZOE sealer [28] and with mineral trioxide aggregate (MTA) [26, 29]. In this case, MTA was selected as a root-filling material because of its biocompatibility, excellent sealing ability, and long-term better prognosis than gutta-percha and ZOE sealer [27]. …”
Section: Discussionmentioning
confidence: 99%